Malignant Hyperthermia in a Morbidly Obese Patient Depletes Community Dantrolene Resources: A Case Report. Issue 9 (1st November 2017) - Magistris, Fabio; Gamble, Jonathan
Abstract : During resection of a duodenal carcinoid tumor, a 28-year-old morbidly obese woman developed suspected malignant hyperthermia. This hypermetabolic state posed a diagnostic challenge given the similar intraoperative presentation of carcinoid crisis and malignant hyperthermia. The patient's weight posed therapeutic challenges as massive doses and prolonged administration of dantrolene were required that quickly depleted the available supply. Current dantrolene dosing recommendations are based on actual body weight despite a paucity of literature in obese patients. We speculate that the prolonged need for dantrolene redosing was from the continuous release of the volatile anesthetic from the patient's adipose tissue.